Analisis Penguasaan Teknologi Informasi dan Komunikasi Guru PJOK Pasca Pandemi Covid-19 - Wasana, Benny Andreadma; Rahayu, Tandiyo; Kusuma, Donny Wira Yudha (Jurnal Sporta Saintika, 2023)
Benny Andreadma Wasana, 2023. "Analysis of Information and Communication Technology Mastery of Physical Education, Sports and Health Teachers in Demak Regency Post Covid-19 Pandemic". Thesis. Sports Education Study Program. Postgraduate. Semarang State University. Supervisor I: Prof. Dr. Tandiyo Rahayu, M.Pd. Supervisor II: Donny Wira Yudha Kusuma, Ph.D. Keywords:ICT Mastery, PE Teacher. Background of the problem: Teachers as learning facilitators must be able to manage teaching and learning activities in such a way that they can achieve learning objectives effectively. Teachers must be able to plan and develop learning models so that learning continues in all circumstances. So the aim of Education 5.0 is to answer the need for information technology and super fast internet so that it can be used to support education. This research uses mixed method. By using designco-embedded (unbalanced mixed combination) through survey and ethnographic methods. With a population of 466 PJOK teachers and sampling techniques used cluster sampling. Then this research uses data triangulation using the Atlas.ti application Research results through: 1) test chi square in the crossstabulation This means that the average Information and Communication Technology ability of PJOK teachers in Demak Regency is stated to be good; 2) the results of interviews with PJOK teacher mastery regarding applications are still low, then supporting facilities and infrastructure are still limited; 3) the results of interviews with PJOK teachers in the Medium category show that the majority of PJOK teachers use laptops/computers as learning support media; 4) the results of interviews with PJOK teachers are in the high category and have been fully implemented starting from the use of laptops/computers, internet, smartphones, school WiFi, Microsoft Office applications, as well as technology-based learning media at the beginning of the year around June-July which are inserted between between giving students daily assignments and remedial work during the Covid-19 pandemic. The conclusion of the research is that the ability of PJOK teachers in Demak Regency in mastering ICT is only 1 person out of 163 teachers has low ability, 124 out of 163 teachers have medium ability, and 38 out of 163 teachers have high ability. It can be concluded that the average Information and Communication Technology abilities of PJOK teachers in Demak Regency are stated to be good.